(NiZBRANNYE SO^INENIQ (B/s - (NlERMONTOW(B, (NmIHAIL `RXEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1983)
(Nw KNIGU WO[LI IZBRANNYE STIHOTWORENIQ I PO\MY (B1828-1841 (NGG(B., (NDRAMY (B"(NsTRANNYJ ^ELOWEK(B", "(NmASKARAD(B", (NROMAN (B"(NgEROJ NA[EGO WREMENI(B" (NI DRUGIE PROIZWEDENIQ W PROZE m(B.(N`(B. (NlERMONTOWA(B.s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\ZIQ(B, (NPO\MYs; (NrUSSKAQ LITERATURAs